Antenatal Care Attendance and Factors Influenced Birth Weight of Babies Born between June 2017 and May 2018 in the Wa East District, Ghana. (20th July 2020) - Appiah, Prince Kubi; Bukari, Mohammed; Yiri-Erong, Simon Nidoolah; Owusu, Kwabena; Atanga, George Borogyante; Nimirkpen, Stephen; Kuubabongnaa, Blaise Bagyliku; Adjuik, Martin
Abstract : Background. In sub-Saharan Africa, there is high coverage of the recommended four or more times antenatal care (ANC) visits during pregnancy without complications; notwithstanding this achievement, the negative birth outcomes related to childbirth such as low birth weights and stillbirths are still high despite the increased access to antenatal services. Hence, the study assessed the association between antenatal attendance and birth weight in the Wa East District. Method. The cross-sectional study design was used with a semistructured questionnaire to collect data from mothers who delivered within a one-year period through a review of antenatal and birth records from health facilities where the women delivered and interviewed. The chi-squared test and univariate and multivariate logistic regression were performed to establish the association between normal birth weight and ANC services the woman received and other predictor variables, and p value < 0.05 was considered a significant association between dependent and independent variables. Result. The study involved 233 women. About 62.2% attended ANC clinics 4+ times before giving birth, 70.0% did not received the minimum ANC services required for every pregnant woman, 0.9% of pregnancies resulted in stillbirth, and 24.5% of babies born had a birth weight < 2.5 kg . Women marital status (legally married) [AOR: 2.05, 95% CI: 1.33-6.89, p = 0.044 ], religion (Islam) [AOR: 0.33, 95% CI: 0.08-0.39, p = 0.013 ], and educational level (SHS/tertiary) [AOR: 4.27, 95% CI: 0.08-0.88, p = 0.031 ] were the background characteristics associated with normal birth weight (2.5-40 kg). Also, women who had their urine tested at the ANC clinics [AOR: 6.59, 95% CI: 8.48–15.07, p < 0.001 ] and women who received a long-lasting insecticide-treated net [AOR: 2.17, 95% CI: 0.03-0.92, p = 0.039 ] from the ANC clinic were associated with normal birth weight. Conclusion. Notwithstanding the benefits of antenatal care services, only 62.2% of pregnant women attended 4 or more ANC visits before giving birth, while 70% did not received the services they need. These might have influence the 24.5% of babies born with a low birth weight. Therefore, there is a need for special attention from all stakeholders to reverse the trend.